Assessing the Impact of Training on Electric Motor Conversion for Sustainable Energy Transition in Indonesia - Taufani Kurniatun; Hertiyo Sembodo; Ahmad Nasarudin; Nurhadi Kusomo; Putria Wardhani Sanfishdah; Stepanus Wisnu Driyaskoro; Muhamad Indra Adriawan; Murtono Anwar (Journal of Education and Teaching (JET), 2025)
This study evaluates the effectiveness of training programs focused on converting fuel-powered motorcycles to electric motorcycles in Indonesia as part of the sustainable energy transition. Using a mixed-methods approach, quantitative data were collected from 31 alumni of the 2022 training cohort, while qualitative insights were gathered through interviews with select participants. Quantitative result reveal that facilities have a positive and significant effect on individual impact, as does training material. However, no significant effect is observed between training syllabus and individual impact. Qualitative results reveal that while the training content is generally effective, regulatory issues, unclear conversion standards, and limited workshop certifications hinder the implementation of learned skills. Participants also noted the need for additional training on electric motorcycle servicing and battery maintenance. The study emphasizes the importance of stronger collaboration between training providers, government agencies, and industries to address these challenges. By improving training curricula, reducing financial barriers, and aligning policies with field needs, this program can further contribute to Indonesia’s renewable energy goals and the development of a skilled workforce in the electric vehicle industry.